Forcings, feedbacks and climate sensitivity in HadGEM3‐GC3.1 and UKESM1 - Andrews, Timothy; Andrews, Martin B.; Bodas‐Salcedo, Alejandro; Jones, Gareth S.; Kuhlbrodt, Till; Manners, James; Menary, Matthew B.; Ridley, Jeff; Ringer, Mark A.; Sellar, Alistair A.; Senior, Catherine A.; Tang, Yongming (Journal of Advances in Modeling Earth Systems, 2020)
Climate forcing, sensitivity and feedback metrics are evaluated in both the UK’s physical climate model HadGEM3-GC3.1at low (-LL) and medium(-MM) resolution and the UK’s Earth System Model UKESM1. The Effective Climate Sensitivity (EffCS)to a doubling of CO2 is 5.5K for HadGEM3.1-GC3.1-LL and 5.4 K for UKESM1. The transient climate response is 2.5K and 2.8K respectively. Whilst the EffCS is larger than that seen in the previous generation of models, none of the model’s forcing or feedback processes are found to be atypical of models, though the cloud feedback is at the high end. The relatively large EffCS results from an unusual combination of a typical CO2 forcing with a relatively small feedback parameter. Compared to the previous UK climate model, HadGEM3-GC2.0, the EffCS has increased from 3.2K to 5.5K due to an increase in CO2 forcing, surface albedo feedback and mid-latitude cloud feedback. All changes are well understood and due to physical improvements in the model.At higher atmospheric and ocean resolution(HadGEM3-GC3.1-MM), there is a compensation between increased marine stratocumulous cloud feedback and reduced Antarctic sea-ice feedback. In UKESM1 a CO2 fertilization effect induces a land surface vegetation change and albedo radiative effect. Historical aerosol forcing in HadGEM3-GC3.1-LL is -1.1 Wm-2. In HadGEM3-GC3.1-LL historical simulations cloud feedback is found to be less positive than in abrupt-4xCO2, in agreement with atmosphere-only experiments forced with observed historical sea-surface-temperature and sea-ice variations. However variability in the coupled model’s historical sea-ice trends hampers accurate diagnosis of the model’s total historical feedback.